93 EFFECT OF SACUBITRIL/VALSARTAN ON ENDOTHELIAL DYSFUNCTION AND ARTERIAL STIFFNESS IN PATIENTS WITH CHRONIC HEART FAILURE. (15th December 2022) - Armentaro, Giuseppe; Cassano, Velia; Magurno, Marcello; Condoleo, Valentino; Monaco, Vittoria; Clausi, Elvira; Divino, Marcello; Pastura, Carlo Alberto; Barbara, Keti; Crescibene, Daniele; Miceli, Sofia; Maio, Raffaele; et al.
Abstract: Aim: Heart failure (HF) is associated to endothelial dysfunction, a pathological condition characterized by imbalance between the production of vasoconstrictor and vasodilator factors, increase in the production of cytokines, down-regulation of eNOS, platelets activation and increased oxidative stress. Furthermore, endothelial dysfunction promotes the increase of arterial stiffness, augmenting myocardial damage. Sacubitril/Valsartan (sac/val) is used in the treatment of HF reduced ejection fraction (HFrEF) and has been proven effective in reducing CV disease progression and all-cause mortality in HFrEF patients. The aim of the study was to evaluate the effect of sac/val on endothelial dysfunction and arterial stiffness in patients with HFrEF, at baseline and after 6 months of treatment. Moreover, we evaluated the effects of sac/val on oxidative stress levels and platelets activation. Materials Methods: We enrolled 46 Caucasian patients (mean age 70.1±7.1), suffering from HFrEF. Inclusion criteria were LVEF<35, functional class NYHA II or III. All clinical evaluation and laboratory tests were performed at baseline and after 6 months of treatment. The serum values of the markers of oxidative stress (8-isoprostane, NOX-2) and platelets activation (Sp-selectin, GPVI) were assessed with ELISA sandwich. Endothelial function was estimated with the measurement of the reactive hyperemia index (RHI); arterial stiffness (AS) was evaluated with the measurement of carotid-femoral pulse wave velocity (PWV), augmentation pressure (AP) and augmentation index (AI). Results: The mean dose of sac/val was 180.5±110 mg without serious adverse events. At 6 months, data showed a significant improvement in in hemodynamic and clinical parameters such as heart rate (HR) (p<0.0001), NT-ProBNP (p<0.0001), fasting plasma glucose (FPG) (p<0.0001). Furthermore, there was a significant reduction in oxidative stress, platelets activation and inflammatory indices. We observed a significant improvement in PWV (p<0.0001), AI (p<0.0001), AP (p<0.0001) and RHI (p<0.0001). A linear correlation analysis was performed to assess the association between vascular parameters and different covariates expressed as Δ variation between baseline and follow-up. ΔPWV was directly correlated with ΔHOMA (p=0.037), ΔIL-6 (p=0.034), ΔTNF-α (p=0.001), Δ8-isoprostane (p=0.016), ΔNox-2 (p=0.01), ΔGP6 (p=0.018), ΔSp-selectin (p=0.023); ΔRHI was inversely correlated with ΔHOMA (p=0.003), ΔIL-6 (p=0.004), ΔTNF-α (p=0.023), ΔCRP (p=0.011), Δ8-isoprostane (p=0.012), ΔNox-2 (p=0.01), ΔGP6 (p=0.014), ΔSp-selectin (p=0.015). From stepwise multivariate linear regression model, ΔTNF-α was the stronger predictor of ΔPWV, justifying 48.5% of its variation and ΔSp-selectin was the major predictor of ΔRHI explaining 23.2% of its variation. Conclusion: The treatment with sac/val improved endothelial dysfunction and arterial stiffness, due to reduced levels of oxidative stress, platelet activation and inflammation.